PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV SDN 07 KUBANG PUTIAH KABUPATEN AGAM - Stevany; Yesi Anita; Arwin; Leni Zahara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the results of observations in the field, namely the low learning outcomes of students due to a lack of learning activities that involve students because the learning process is still centered on the teacher, so that students passive during the learning process. This research aims to describe how to improve student learning outcomes in Pancasila education learning using the Problem Based Learning (PBL) model in Class 7V SDN 01 Kubang Putiah Agam Regency. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. This research was carried out in two cycles, with research procedures consisting of planning, implementation, observation and reflection. The research data obtained is related to the learning outcomes of the Problem Based Learning model. Data collection techniques include tests and non-tests. The subjects of this research were class teachers as observers, researchers as practitioners or teachers, and 20 class IV students at SDN 07 Kubang Putiah Agam Regency. The research results showed that: First, the teaching module for cycle I obtained an average of 85,4% (B), increasing in cycle II to 95,8% (SB). Second, the results of the teacher aspect of learning in cycle I obtained an average of 82,14% (B), increasing in cycle II to 96,42% (SB). Third, the results of the implementation of learning aspects for students in cycle I obtained an average of 78,56% (C), increasing in cycle II to 92,85% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 73,5 (C), increasing in cycle II to 88 (B). Thus, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in Pancasila education learning in class IV at SDN 07 Kubang Putiah Agam Regency.